Holocene Monsoonal Variations Over Southern India: Looking Into Its Antecedents - Resmi, M. R.; Achyuthan, Hema; Deopa, Hritika (Frontiers in Earth Science, 2022)
A proper understanding of the paleoclimatic variability in the Southern Peninsular India demands a high-resolution paleoclimate reconstruction. Hence, in this paper we compiled all the available paleoclimate record from various locations across the Southern India that receive the southwest and the northeast monsoon. We delineated the monsoonal variations i.e., southwest monsoon (SWM) and Northeast monsoon (NEM) within the Holocene Period based on the literary records and the current data available. Paleoclimate records are based on various paleoclimate archives and proxies. A detailed study of these variations unravels, (i) that SWMR gradually intensified since the younger dryas during the Early Holocene period. On the contrary, NEMR records indicate a dry phase during the same period. (ii) however, since the mid-Holocene to recent period, SWMR and NEMR exhibit a positive correlation of dry phase with short intervals of wetter pulses. (iii) In late Holocene Period, shows an overall wet phase for SWMR and dry phase for the NEMR. The overall dry phase in Southern Indian is coeval with the demise of the Chola dynasty and the Bronze age with lower sea-level.